Let’s publish full-text scientific articles in HTML, not just PDF - Libor Ansorge (European Science Editing)
The digital age has enabled unprecedented opportunities in the dissemination of information. Thanks to the Internet, research results are available to virtually anyone in the world. Thanks to platforms such as the Open Journal System, a scientific journal can be published by practically anyone with minimal demands on resources, and even a relatively small editorial team can focus more on the quality of published articles than on the editorial process itself. Nevertheless, publishing procedures have recently been adopted which do not allow parts of readers to have seamless access to the content of scientific articles.